About Noguchi recent research about the specific agent of yellow fever - Arce, Julián (1919)
The study of the etiology of infectious diseases has always had as main objective research and identification of the corresponding causative organism. The work undertaken to this end have been inspired, of course, the doctrines and the methods proper to the period in which they were made, which explains the numerous findings, prematurely considered as definitive, which records the history of many of these diseases, the specific cause today is resisting the wonderful advances in science and still remains a mystery. The yellow fever typhus, is a demonstrative example of what you just said. Indeed, just created bacteriology, Freire Rio de Janeiro in 1883, he thought he had discovered the germ of this scourge, a micrococcus which isolated and studied under the name Cryptococcus xanthogenicus; prepared immediately cultures attenuated the bacterium, with whom he practiced preventive inoculations and presented statistics at first comprobatorias view of the prophylactic efficacy of the vaccine, whose use recommended later the International Congress of Hygiene and Demography, held at Buda-Pesth in 1894.